The Mediating Effects of Anxiety and Happiness and the Moderating Effect of Social Network Services for Employee Silence and Psychological Withdrawal Behavior - Xue Tong Dong; Yang Woon Chung; Jeong Kwon Yun (SAGE Open, 2023)
Employees not being able to express their thoughts and opinions about work has been argued to result in detrimental organizational outcomes. Employee silence has recently become a prevalent organizational issue but studies that have explored proximal and distal outcomes of silence are scarce. Therefore, the study explored anxiety and happiness as mediating mechanisms for the relationship between silence and psychological withdrawal and the moderating effect of social network services usage for the relationship between silence and the mediators. The study conducted a two-wave self-reported questionnaire and sampled 257 full-time employees. Anxiety and happiness were found to mediate the relationship and social network services moderated the relationships between silence with the mediators. Moreover, supplementary analysis found mediated moderation for the study.